2011
DOI: 10.1371/journal.pone.0024570
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Bacterial Beta-Diversity in Seafloor and Seawater Ecosystems

Abstract: BackgroundMarine microbial communities have been essential contributors to global biomass, nutrient cycling, and biodiversity since the early history of Earth, but so far their community distribution patterns remain unknown in most marine ecosystems.Methodology/Principal FindingsThe synthesis of 9.6 million bacterial V6-rRNA amplicons for 509 samples that span the global ocean's surface to the deep-sea floor shows that pelagic and benthic communities greatly differ, at all taxonomic levels, and share <10% bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
424
4
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(509 citation statements)
references
References 68 publications
72
424
4
9
Order By: Relevance
“…As a mixing environment between terrestrial and marine habitats, the coastal area is thought to have a significantly higher diversity of bacterial community than marine sediment (Allen et al 2009;Zinger et al 2011). Our results identified 17 bacterial phyla in the sediments of Jiaozhou Bay.…”
Section: Bacterial Taxonomic Diversity In Jiaozhou Bay Sedimentsmentioning
confidence: 65%
“…As a mixing environment between terrestrial and marine habitats, the coastal area is thought to have a significantly higher diversity of bacterial community than marine sediment (Allen et al 2009;Zinger et al 2011). Our results identified 17 bacterial phyla in the sediments of Jiaozhou Bay.…”
Section: Bacterial Taxonomic Diversity In Jiaozhou Bay Sedimentsmentioning
confidence: 65%
“…Sequences, which could not be assigned to bacteria or archaea, were discarded. OTUs were defined using a distance matrix with 3% dissimilarity (Zinger et al 2011). Data analysis was performed using mothur software package version 1.31.2 (http://www.mothur.org/) following the standard operational procedure (SOP) (Schloss et al 2009).…”
Section: Illumina Amplicon Sequencingmentioning
confidence: 99%
“…The present study shows that Acidobacteria and Proteobacteria are also predominant in the soil of tropical forests in Indonesia (Java and Sumatra) and Singapore in Southeast Asia. Acidobacteria and Proteobacteria are Gram-negative bacteria represented by many species that grow and survive under many environmental conditions (Stackebrandt et al, 1988;Quaiser et al, 2003); however, Acidobacteria are found primarily in soil (Sogins et al, 2006), while Proteobacteria are found in soil (Barns et al, 1999;Zinger et al, 2011;Wang et al, 2012), fresh water (Hugenholtz et al, 1998) and seawater (Hugenholtz et al, 1998;Venter et al, 2004;Zinger et al, 2011). In BKOman, an exceptional phylum composition was observed, characterized by high representation of Proteobacteria (≈40%) and low representation of Acidobacteria (4%).…”
Section: Discussionmentioning
confidence: 99%